Exploring the impact of service recovery on customer affection, perceived value, and sabotaging behaviour: does gender make a difference? - Daskin, Mustafa; Kasim, Azilah (Inderscience Enterprises Ltd., 2016)
This empirical study aims to investigate the impact of service recovery on customer affection, perceived value, and sabotaging behavior in a service industry context in Penang/Malaysia.Data for this empirical investigation were gathered from a sample of international hotel guests.A total number of 248 questionnaires were obtained in the research location.Results based on hierarchical regression analysis reveal that all hypothesized relationships were supported.Specifically, the current study by examining untested relationships such as the effect of service recovery on customer perceived value and sabotaging behavior in a hotel context lends further contribution to tourism and hospitality management literature and provides useful guidelines to practitioners as well.